#TITLE_ALTERNATIVE# - SISWANTO (NIM 12902015), HADI
Current analysis was conducted at coastal water of Kanci, Cirebon to know the current characteristic in that area. Separation of total current became tidal current and non tidal current was done by using computer program (Tan and Tans) which based on Least square method. Field observation was carry out at one station with two depths since 10 July 2007 until 15 August 2007 by using Valeport Current Meter and FSI Acoustic Current Meter. The harmonic analysis results show tidal current at flood move to Northwest - North, while at ebb move to Southeast - South. Maximum velocity of tidal current at 1.5 meter depth is 0.2 m/second with 333.15 degrees directions while maximum velocity at 5.5 meter depth is 0.203 m/second with 340 degrees directions. maximum velocity of non tidal current at 1.5 meter depth is 0.28 m/second with 337.02 degrees directions, while maximum velocity at 5.5 meter depth is 0.288 m/second with 345 degrees directions. Generally velocity of tidal current at both depths has not big different or almost the same value.